PREPARATION OF FURAN EPOXY 3FAMED RESINS (Scientific journal of the Fergana State University, 2023)
The article describes the preparation of furfural-acetone monomers FAM; 2FAM; 3FAM and preparation of furan epoxy resins, polymer composition.